Improving teamwork in maternity services: A rapid review of interventions. (May 2022) - Harris, Jenny; Beck, Sarah; Ayers, Nicola; Bick, Debra; Lamb, Benjamin W.; Aref-Adib, Mehrnoosh; Kelly, Tony; Green, James S.A.; Taylor, Cath
Highlights: Effective teamwork is an essential component of high-quality maternity care. Teamwork intervention are available in maternity, focused on obstetric emergencies. Interventions lack the meso (organisational) and macro (systems) team features. Evidence-based team interventions that address these gaps are needed. ABSTRACT: Background: Teamwork is essential for providing safe, effective and women-centred maternity care and several high profile investigations have highlighted the adverse conseqences of dysfuntional teamwork. Maternity teams may need support to identify the most relevant intervention(s) for improving teamwork. Objective: To identify and describe current 'off-the-shelf' teamwork interventions freely or commercially available to support improvements to teamworking in UK maternity services and conduct a gap analysis to identify areas for future development. Design: Rapid scoping review Methods: A multi-component search process was used to identify teamwork interventions, comprising: (1) bibliographic database search (Medline, PsycINFO, CINAHL, MIDRS, NICE evidence research database); (2) identification of relevant policies and UK reports; and (3) expert input from key stakeholders (e.g., maternity service clinicians, managers, policymakers, and report authors). Data were extracted including the scope and content of each intervention and a gap analysis used to map interventions to the integrated team effectiveness model (ITEM) and structure level (macro, meso, micro) and results presented narratively. Findings: Ten interventions were identified. Interventions were heterogeneous in their purpose and scope; six were classified as training courses, three were tools involving observational or diagnostics instruments, and one was a programme involving training and organisational re-design. Interventions were focused on teamwork in obstetric emergencies ( n  = 5), enhancing routine care ( n  = 4) or understanding workplace cultures ( n  = 1). Users of interventions could vary, from whole organisations, to departments, to individual team members. All interventions focused on micro (e.g., team leadership, communication, decision-making, cohesion, and problem solving), with two also focused on meso aspects of teamwork (resources, organisational goals). Evidence for intervention effective on objective outcomes was limited. Conclusions: Interventions that address key aspects of teamworking are available, particularly for improving safety in obstetric emergency situations. Most interventions, however, are focused on micro features, ignoring the meso (organisational) and macro (systems) features that may also impact on team effectiveness. Evidence-based team improvement interventions that address these gaps are needed. Such interventions would support team ownership of quality improvement, leading to improvements in outcomes for service users, staff and organisations.